Pelatihan Akuntansi Bagi Karang Taruna Sebagai Upaya Peningkatan SDM Dusun Bolu Kecamatan Seyegan - Ninik Tri Hartanti; Mei Maemunah; Emigawaty Emigawaty; Laksmindra Saptyawati; Nur’aini Nur’aini; Sri Mulyatun (Journal of Community Development, 2023)
Yogyakarta is a province that has many features, both cultural and natural. One of the factors driving the economic growth of a region is the agricultural sector, which can be a promising opportunity, apart from being a producer of economic growth it can also have the opportunity to be a driver of growth in other development sectors in an area. One of them is the expansion of the agro-tourism business from Bolu hamlet, Seyegan sub-district, Yogyakarta, which will empower the younger generation, especially youth organizations, as managerial actors in tourism villages. Improving financial management skills for the community, especially in agro-tourism villages, is one of the solutions to existing problems. Through this community service activity, it is hoped that the community, especially youth organizations, will understand the concept and meaning of a cash book, namely a financial journal that contains notes on cash receipts and payments, and understand the benefits of a cash book, namely being able to know the financial condition of a business based on detailed and consistent recording. , as well as a reference to see which part of the business can be the biggest sales driver or discover what causes the biggest expenses. The result of this community service activity is to add insight to the community, especially youth organizations about the bookkeeping system, recording daily transactions so that the business being carried out can provide the expected benefits.